Developing the education research capability of education-focused academics: building skills, identities and communities. Issue 6 (19th September 2022) - Whitton, Joy; Parr, Graham; Choate, Julia
ABSTRACT: This article critically investigates the impact of a program of professional learning for education-focused academics (EFAs) in an Australian university, focused on developing their education research capability. The 'Higher Education Research' (HER) program employed a three-pronged strategy: skills development workshops; sustained small group mentoring; and a small-scale education research study. The aim of the program was to support the university to improve the quality of education by fostering the scholarship of teaching and learning (SoTL). The program was completed by two cohorts of EFAs, in 2014 and 2017. The design of the program was informed by literature showing the value of SoTL in developing the quality of university teaching and the importance of collaborative peer learning structures in supporting SoTL activities. Using Engeström's activity theory and Lave and Wenger's conception of peripheral participation in communities of practice, the study analysed quantitative and qualitative data collected immediately after the HER program and focus group interview data collected at least two years later, to examine the impact over time of the HER program on the participants' careers and identities. This article focuses on five major themes that emerged from the data: struggle – personal-professional struggles experienced by academics in negotiating a shift from their cognate discipline to education as a discipline; identity – changes in identity that academics experienced through participating in the HER program; social relations – factors that contributed to the social experience of learning and developing as a researcher in a complex socio-cultural context; leadership – ways in which the HER program helped participants to develop as leaders; and criticality in educational practice – ways in which academics came to see their work as university educators in more critical terms. The article concludes with recommendations for cross-faculty programs that build higher education educators' skills and knowledge through researching teaching and learning.